A case for serial examination of sputum inflammatory cells. - Wong, A; Pavord, I; Sears, MR; Hargreave, F (1996)
In the case reported, serial evaluation of sputum inflammatory cell counts made it possible to identify an unusual series of events in a man with eosinophilic bronchitis. The patient initially presented with a productive cough, which did not respond to treatment with antibiotics or high-dose inhaled corticosteroids. A diagnosis of eosinophilic bronchitis was made after demonstration of intense sputum eosinophilia. When inhaled corticosteroids were stopped, symptoms and sputum eosinophilia became worse and airway hyperresponsiveness developed. Both abnormalities were reversed by a course of prednisone. When the prednisone was stopped the productive cough recurred but on this occasion sputum examination suggested a different disease process and the symptoms resolved after a course of co-trimoxazole. The patient has subsequently remained well on no treatment with little or no sputum eosinophilia.